2021
DOI: 10.1287/serv.2021.0283
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Hotel Productivity Changes: An Empirical Analysis Using Malmquist Productivity Index

Abstract: This research investigates the impact of COVID-19 on hotel productivity change using the Malmquist Productivity Index (MPI). For 26 U.S. hotel brands, productivity changes over 10 quarters from the first quarter of 2018 to the second quarter of 2020 were analyzed. After the COVID-19 outbreak, the investigated hotels’ productivity deteriorated. Decomposition revealed that, whereas technical efficiency change (EC) improved, technological change (TC) regressed, resulting in deterioration of the MPI. The investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This formula can be rewritten as shown below and decomposed into two components: an efficiency change component (EFFCH) and a technical change component (TECH) of productivity change (Fare, Grosskopf, & Margaritis, 2011;Mohammadi & Ranaei, 2011;Kim et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This formula can be rewritten as shown below and decomposed into two components: an efficiency change component (EFFCH) and a technical change component (TECH) of productivity change (Fare, Grosskopf, & Margaritis, 2011;Mohammadi & Ranaei, 2011;Kim et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…According to Fare et al (1994Fare et al ( , 2011 and Tone (2004), an EFFCH measures the relative deviation from the production frontier, which indicates how efficiently a DMU transforms inputs into outputs from maximum potential production between period t and period t þ 1. A hotel may facilitate its improvement in EFFCH when allocating the inputs more efficiently under the existing technology (Kim et al, 2021). Furthermore, a TECH measures the production frontier shift between period t and period t þ 1.…”
Section: Malmquist Productivity Index (Mpi) = An Efficiency Change Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lockdowns affect several industries. Tourism and the related industries are prominent examples ( de Vries et al, 2021 ; Hao et al, 2021 ; Kim et al, 2021 ). Studies also indicate that agriculture is an industry affected by lockdowns due to delayed harvest ( Golban & Golban, 2021 ; Mohanty et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the dependence on human resources is relatively high and that the role of industrial workers is critical [5]. Therefore, the threat to human resources in the service industry due to the pandemic can lead to a decline in the quality of services, which may eventually affect the hotel's corporate productivity [6]. In other words, companies must solve job insecurity or manage job stress to improve corporate productivity.…”
Section: Introductionmentioning
confidence: 99%